Additive for prebaked anode and application thereof
By using additives composed of boric acid, carbon black and stabilizer in the pre-baked anode, the consumption problem caused by high reactivity in the production of electrolytic aluminum is solved, and the effect of reducing carbon and electricity consumption is achieved.
Patent Information
- Application Number
- CN202411090100.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2025-03-11
AI Technical Summary
In the production of electrolytic aluminum, the consumption of existing pre-baked anodes increases due to high air reactivity and CO2 reactivity, affecting the anode mass and increasing carbon emissions.
The additives composed of boric acid, carbon black and stabilizer are used to reduce the oxidation speed and reactivity of the anode by adjusting the crystalline morphology of the anode, improving the conductivity and mechanical properties, and maintaining the uniformity and structural stability of the material.
It significantly reduces the air reactivity and CO2 reactivity of the pre-baked anode, extends the service life of the anode, and reduces the carbon and electricity consumption in the electrolytic aluminum production.
Smart Images

Figure BDA0004986294150000081 
Figure BDA0004986294150000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of prebaked anodes for aluminum electrolysis, and in particular relates to an additive for prebaked anodes and application thereof. Background Art
[0002] As a carbon material, prebaked anode has good electrical conductivity, high temperature resistance and corrosion resistance. It plays a vital role in the production of electrolytic aluminum, including conducting electricity, participating in electrochemical reactions and providing high current density. It is one of the core materials for electrolytic aluminum production and is called the "heart" of the electrolytic cell. However, in the process of electrolytic aluminum, the consumption of prebaked anode consists of electrochemical consumption and excess consumption. Excess consumption includes air reaction consumption, CO2 reaction consumption, partial slag and aluminum electrolysis side reaction consumption. Among the many factors affecting the quality of prebaked anode, the air reactivity and CO2 reactivity of prebaked anode have the greatest impact on the quality of prebaked anode. The reaction of prebaked anode with air usually occurs on the top and exposed side of the prebaked anode: C+O2=CO2, 2C+O2=2CO. The reaction of prebaked anode with CO2 is because the anode is a porous structure material. The CO2 produced by the electrochemical reaction can penetrate into the anode through the interface between the anode and the molten salt, thereby causing the Boudor reaction: C+CO2=2CO. Therefore, in aluminum electrolysis production, improving the oxidation resistance of prebaked anodes and reducing the air reactivity of prebaked anodes can significantly reduce the carbon consumption of prebaked anodes, reduce CO2 emissions, and also reduce the production cost of aluminum.
[0003] The use of high-quality additives can effectively improve the antioxidant properties of prebaked anodes. At present, there are fewer additives for prebaked anodes. The reason is that the selection and addition amount of additives need to be strictly optimized to balance the relationship between performance improvement and cost-effectiveness. Secondly, the mechanism of action of the additives and their distribution state in the anode material have an important influence on the final antioxidant effect, which requires in-depth research and exploration. CN111041527A discloses a method for preparing a prebaked anode for aluminum modified with rare earth additives. A total amount of 0.1-0.5% of rare earth carbonate, cerium carbonate, lanthanum carbonate, and lanthanum cerium carbonate is added to the anode paste. The obtained product can effectively reduce the catalytic oxidation effect of the trace element vanadium in the anode on the anode and improve the antioxidant capacity of the anode. Although there have been some studies on the antioxidant properties of prebaked anodes, the application of new additives in prebaked anodes still faces some challenges and limitations.
[0004] Therefore, in order to overcome the limitations of the existing technology for improving the antioxidant properties of prebaked anodes, it is necessary to research and develop a preparation and application solution for prebaked anode additives, aiming to provide the electrolytic aluminum industry with a more reliable and economical high-quality prebaked anode solution and promote the further development and upgrading of prebaked anode and electrolytic production technology. Summary of the invention
[0005] Based on the above technical background, the present invention provides an additive for prebaked anode and its application. The additive is composed of boric acid, carbon black and stabilizer. The additive can increase the reaction difficulty of carbon and reduce carbon consumption, and convert carbon to a direction with a high degree of graphitization. Secondly, boric acid is used to adjust the crystal morphology of the prebaked anode during the baking process, effectively slowing down the oxidation rate of the anode in the electrolytic cell; adding carbon black improves the conductivity of the anode, enhances the mechanical properties of the anode, and reduces the possibility of cracks; different stabilizers are selected to maintain the uniformity and structural stability of the anode material, and expand the scope of use of the additive. The use of this additive can effectively inhibit the oxidation of prebaked anodes and extend the service life of anodes.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] An additive for prebaked anodes, comprising the following components by weight percentage:
[0008] Boric acid: 30-60%;
[0009] Carbon black: 1-11%;
[0010] Stabilizer: 29-69%.
[0011] Furthermore, the stabilizer is one or more of aluminum silicate, aluminum fluoride, magnesium carbonate, magnesium oxide and mullite; the stabilizer is in the form of white powder, with an effective ingredient content of more than 99.8% and a particle size of ≤2000 mesh.
[0012] A method for preparing an additive for prebaked anodes comprises the following steps: uniformly mixing and blending various raw material components according to weight percentage to obtain the additive.
[0013] Furthermore, the boric acid is in the form of white crystalline particles and powder, which can adjust the crystal morphology of the prebaked anode during the calcination process, help form a more uniform and stable structure, improve the electrical conductivity of the anode, increase the electrical conductivity, thereby reducing energy loss, and help slow down the oxidation rate of the anode in the electrolytic cell, thereby extending the service life of the anode.
[0014] Furthermore, the carbon black is a black powdery substance mainly composed of elemental carbon and containing a small amount of oxygen, hydrogen and sulfur. Carbon black is a highly conductive material with good mechanical strength and wear resistance. Adding carbon black can improve the conductivity of the prebaked anode, enhance the mechanical properties of the prebaked anode, and improve its compressive resistance and durability. In addition, carbon black helps to improve the uniformity of the anode, help the prebaked anode absorb heat and withstand pressure more evenly, and reduce the possibility of cracks.
[0015] Furthermore, the aluminum silicate has high heat resistance, and can increase the high temperature resistance of the prebaked anode during the baking process, help maintain the structural stability of the anode, and prevent the anode from deforming or cracking at high temperatures.
[0016] Furthermore, the aluminum fluoride can promote the crystal growth of the anode material during the anode baking stage, help form a more uniform and stable lattice structure, and improve the performance and strength of the anode. Since aluminum fluoride has good electrical conductivity, adding an appropriate amount of aluminum fluoride can improve the electrical conductivity of the anode, reduce resistance, and reduce energy loss. In addition, aluminum fluoride can prevent excessive growth and aggregation of graphite particles, thereby maintaining the uniformity and stability of the anode material.
[0017] Furthermore, the magnesium carbonate can reduce the graphitization tendency of the anode material during the roasting process, promote the formation of the lattice structure of the anode material, improve the microstructure of the anode, maintain uniformity and consistency inside the anode material, improve strength and stability, increase mechanical strength, improve heat resistance and pressure resistance, and make the anode more stable and reliable in the electrolytic cell.
[0018] Furthermore, the magnesium oxide has good thermal shock resistance, and adding an appropriate amount of magnesium oxide can improve the heat resistance of the anode, reduce microcracks and damage caused by temperature changes, and extend the service life of the anode. Magnesium oxide itself is an insulating material, but it can interact with other conductive materials during the roasting process, thereby improving the conductivity of the anode, reducing impedance, and improving the conductivity of the anode.
[0019] Furthermore, the mullite has high thermal stability, and adding an appropriate amount of mullite can improve the high temperature resistance of the anode material. It helps to reduce the thermal expansion coefficient of the anode material, reduce deformation and thermal cracking at high temperatures, and mullite, as an additive component, can promote the redox reaction between the anode and aluminum oxide in the electrolyte and improve the electrolysis efficiency.
[0020] Principle of action: During the oxidation of carbon, C reacts with O2 to generate CO2. At the same time, in a high-temperature, high-carbon and low-oxygen environment, a C / CO2 reaction will continue to consume carbon. In order to increase the difficulty of carbon reaction and reduce carbon consumption, converting carbon to a direction with a high degree of graphitization is an effective means. In the process of producing anodes, the presence of boron in boric acid can promote the graphitization process of carbon, the presence of carbon black can promote the entry of boron into the carbon ring, and further catalyze the graphitization reaction of carbon, while the presence of stabilizers will increase the reaction barrier of the anode C / CO2 reaction in the electrolytic cell. Secondly, based on the performance and characteristics of the material itself, boric acid is used to adjust the crystal morphology of the prebaked anode during the baking process, effectively slowing down the oxidation rate of the anode in the electrolytic cell; adding carbon black improves the conductivity of the anode, enhances the mechanical properties of the anode, and reduces the possibility of cracks; different stabilizers are selected to maintain the uniformity and structural stability of the anode material, and expand the scope of use of additives. Under the synergistic effect of multiple raw materials, additives can effectively increase the high oxidation resistance and high thermal shock resistance of the prebaked anode, and optimize the performance of the anode in the electrolytic cell.
[0021] The invention also provides an application of the additive in the preparation of a prebaked anode.
[0022] A method for applying an additive in the preparation of a prebaked anode comprises the following steps:
[0023] S1: Batching: Accurately calculate the amount of each component of the anode paste, including 80-90% aggregate and 10-20% binder by weight; weigh calcined petroleum coke, anode particles, and anode fine powder respectively, mix them evenly to make aggregate;
[0024] S2: Kneading: Add 0.1-2% additives to the aggregate prepared in step S1, dry-mix in a kneader to obtain a uniformly mixed dry mixed material; then add the preheated binder and wet-mix to obtain a uniformly kneaded anode paste;
[0025] S3: Molding: The anode paste obtained in step S2 is conveyed to a vibration molding machine for molding to form an anti-oxidation prebaked anode green body;
[0026] S4: calcining: placing the pre-baked anode green body obtained in step S3 in a calcining furnace and calcining it according to a set process heating curve;
[0027] S5: Finished product: After roasting, the temperature is cooled to below 200°C, and the metallurgical coke is removed from the furnace and cleaned to obtain an anti-oxidation prebaked anode.
[0028] Furthermore, the aggregate in step S1 comprises 86-94% calcined petroleum coke, 4-8% anode particles, and 2-6% anode fine powder by weight.
[0029] Furthermore, the calcined petroleum coke in step S1 is composed of a mixture of calcined coke particles of different particle sizes, wherein by weight percentage, 6# coke particles with a particle size of 6-3mm account for 30-40%, 3# coke particles with a particle size of 3-1mm account for 30-50%, and 1# coke particles with a particle size of 1-0.075mm account for 10-40%; the particle size of the anode particles is 7-9mm; and the particle size of the anode fine powder is 200-300 mesh.
[0030] Furthermore, the binder in step S2 is coal tar, with a softening point of 103-110° C. and a coking value of 56-59%.
[0031] Furthermore, in step S2, the dry mixing time is 15-20 minutes, the preheating temperature is 178-186° C., and the wet mixing time is 15-20 minutes.
[0032] Furthermore, the process control parameters of the roasting step in step S4 are: heating rate of 7-10°C / h in low and high temperature stages, heating rate of 6-11°C / h in medium temperature stage, the highest temperature of the roasting curve is 1140-1200°C, the highest temperature of the sample is 1050-1080°C, and the heat preservation is 48-84h.
[0033] Beneficial effects:
[0034] (1) The additive prepared by the present invention significantly reduces the air reactivity and CO2 reactivity of the anti-oxidation prebaked anode in the electrolytic cell, effectively reduces the consumption of the anode and prolongs the service life of the prebaked anode.
[0035] (2) This additive can reduce the resistivity of the anode, thereby reducing the voltage of the electrolytic cell, improving the efficiency of the electrolytic current, and comprehensively improving the performance of the anode, thereby achieving the purpose of reducing power consumption and carbon consumption in production; secondly, the raw materials can be derived from the waste of pre-baked anodes produced by traditional processes, thereby achieving the recycling of waste materials, which is in line with the current direction of green, sustainable and high-quality development.
[0036] (3) The additive formula has been optimized and designed to have good stability and controllability. It can work stably under different process conditions and is compatible with existing production processes. It is easy to promote and apply in large-scale production. DETAILED DESCRIPTION
[0037] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be specifically described below in conjunction with the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0038] 1. Source of raw materials:
[0039] Boric acid was purchased from Liaocheng Everbright Chemical Co., Ltd., carbon black was purchased from Zibo Dingsheng Power Materials Co., Ltd., aluminum silicate was purchased from Lingshou Rongyu Mineral Products Co., Ltd., aluminum fluoride was purchased from Jiangxi Wangshang Environmental Protection Technology Co., Ltd., and magnesium carbonate was purchased from Qiwei Chemical Co., Ltd.; petroleum coke was purchased from Sinopec Refining and Sales Co., Ltd., and coal tar was purchased from Xingtai Xuyang Coal Chemical Co., Ltd.
[0040] 2. Raw material preparation:
[0041] (1) The preparation process of 6# coke pellets, 3# coke pellets and 1# coke pellets is as follows:
[0042] a. Calcination of petroleum coke: The volatile matter of petroleum coke is controlled at 8.0-12.0%, and the blended petroleum coke is calcined at a high temperature of 1250-1350°C in a downstream pot calciner to obtain calcined petroleum coke;
[0043] b. Crushing and screening: The calcined petroleum coke is crushed and screened using a vibrating screen to obtain 6# coke particles with a particle size of 6-3mm, 3# coke particles with a particle size of 3-1mm, and 1# coke particles with a particle size of 1-0.075mm.
[0044] (2) The preparation process of anode granules and anode fine powder is as follows:
[0045] a. Crushing: The waste pre-baked anodes from the existing traditional process are crushed into 6-8cm using a high-pressure crusher, then crushed using a pair of rollers, and a vibrating screen is used to screen out anode particles with a particle size of 7-9mm;
[0046] b. Grinding: After screening, the anode particles smaller than 7mm enter the Raymond mill to produce anode fine powder with a particle size of 200-300 mesh.
[0047] 3. Additive formula setting
[0048] Formula 1-6 can be prepared by mixing and blending the following raw material components evenly.
[0049] Formula 1: 7.87 g boric acid, 1.74 g carbon black, 10.39 g aluminum silicate;
[0050] Formula 2: 11.73 g boric acid, 1.40 g carbon black, 6.87 g aluminum silicate;
[0051] Formula 3: 7.87 g boric acid, 1.74 g carbon black, 10.39 g aluminum fluoride;
[0052] Formula 4: 11.07 g boric acid, 2.07 g carbon black, 6.87 g aluminum fluoride;
[0053] Formula 5: 11.75 g boric acid, 1.50 g carbon black, 4.42 g aluminum silicate, 2.33 g magnesium carbonate;
[0054] Formula 6: 8.75 g boric acid, 1.04 g carbon black, 5.63 g aluminum silicate, 4.58 g magnesium carbonate.
[0055] Example 1
[0056] An application of an additive in the preparation of a prebaked anode comprises the following steps:
[0057] S1: Batching: Accurately calculate the amount of each component of the anode paste, including 1680g of aggregate and 320g of binder; weigh 1546g of calcined petroleum coke (including 541g of 6# coke particles with a particle size of 5mm, 541g of 3# coke particles with a particle size of 2mm, and 464g of 1# coke particles with a particle size of 0.075mm), 84g of anode particles with a particle size of 8mm, and 50g of anode fine powder with a particle size of -200 mesh, and mix them evenly to form the aggregate;
[0058] S2: Kneading: Add 20g of the additive formula 1 to the aggregate prepared in step S1, and dry-mix in a kneader for 15min to obtain a uniformly mixed dry mixed material; then add 320g of coal tar pitch (softening point of 105°C, coking value of 58%) preheated to 180°C and wet-mix for 20min to obtain a uniformly kneaded paste;
[0059] S3: Molding: The anode paste obtained in step S2 is conveyed to a vibration molding machine for molding to form an anti-oxidation prebaked anode green body;
[0060] S4: calcination: the pre-baked anode green body obtained in step S3 is placed in a calcination furnace and calcined according to the set process heating curve: the heating rate in the low and high temperature stages is 8°C / h, the heating rate in the medium temperature stage is 10°C / h, the highest temperature of the calcination curve is 1160°C, the highest temperature of the sample is 1050°C, and the temperature is kept for 72h;
[0061] S5: Finished product: After roasting, the temperature is cooled to 180°C, and the metallurgical coke is cleaned out of the furnace to obtain an anti-oxidation pre-baked anode.
[0062] Example 2
[0063] An application of an additive in the preparation of a prebaked anode comprises the following steps:
[0064] S1: Batching: Accurately calculate the amount of each component of the anode paste, including 1680g of aggregate and 320g of binder; weigh 1546g of calcined petroleum coke (including 541g of 6# coke particles with a particle size of 5mm, 541g of 3# coke particles with a particle size of 2mm, and 464g of 1# coke particles with a particle size of 0.075mm), 84g of anode particles with a particle size of 8mm, and 50g of anode fine powder with a particle size of -200 mesh, and mix them evenly to form the aggregate;
[0065] S2: Kneading: Add 20g of additive formula 2 to the aggregate prepared in step S1, dry-mix in a kneader for 15min to obtain a uniformly mixed dry mixed material; then add 320g of coal tar pitch (softening point of 105℃, coking value of 58%) preheated to 180℃ and wet-mix for 20min to obtain a uniformly kneaded paste;
[0066] S3: Molding: The anode paste obtained in step S2 is conveyed to a vibration molding machine for molding to form an anti-oxidation prebaked anode green body;
[0067] S4: calcination: the pre-baked anode green body obtained in step S3 is placed in a calcination furnace and calcined according to the set process heating curve: the heating rate in the low and high temperature stages is 9°C / h, the heating rate in the medium temperature stage is 8°C / h, the highest temperature of the calcination curve is 1180°C, the highest temperature of the sample is 1060°C, and the temperature is kept for 48h;
[0068] S5: Finished product: After roasting, the temperature is cooled to 180°C, and the metallurgical coke is cleaned out of the furnace to obtain an anti-oxidation pre-baked anode.
[0069] Example 3
[0070] An application of an additive in the preparation of a prebaked anode comprises the following steps:
[0071] S1: Batching: Accurately calculate the amount of each component of the anode paste, including 1680g of aggregate and 320g of binder; weigh 1546g of calcined petroleum coke (including 541g of 6# coke particles with a particle size of 5mm, 541g of 3# coke particles with a particle size of 2mm, and 464g of 1# coke particles with a particle size of 0.075mm), 84g of anode particles with a particle size of 8mm, and 50g of anode fine powder with a particle size of -200 mesh, and mix them evenly to form the aggregate;
[0072] S2: Kneading: Add 20g of additive formula 3 to the aggregate prepared in step S1, and dry mix in a kneader for 15min to obtain a uniformly mixed dry mixed material; then add 320g of coal tar pitch (softening point of 105°C, coking value of 58%) preheated to 180°C and wet mix for 20min to obtain a uniformly kneaded paste;
[0073] S3: Molding: The anode paste obtained in step S2 is conveyed to a vibration molding machine for molding to form an anti-oxidation prebaked anode green body;
[0074] S4: calcination: the pre-baked anode green body obtained in step S3 is placed in a calcination furnace and calcined according to the set process heating curve: the heating rate in the low and high temperature stages is 9°C / h, the heating rate in the medium temperature stage is 7°C / h, the highest temperature of the calcination curve is 1150°C, the highest temperature of the sample is 1080°C, and the temperature is kept for 80h;
[0075] S5: Finished product: After roasting, the temperature is cooled to 180°C, and the metallurgical coke is cleaned out of the furnace to obtain an anti-oxidation pre-baked anode.
[0076] Example 4
[0077] An application of an additive in the preparation of a prebaked anode comprises the following steps:
[0078] S1: Batching: Accurately calculate the amount of each component of the anode paste, including 1680g of aggregate and 320g of binder; weigh 1546g of calcined petroleum coke (including 541g of 6# coke particles with a particle size of 5mm, 541g of 3# coke particles with a particle size of 2mm, and 464g of 1# coke particles with a particle size of 0.075mm), 84g of anode particles with a particle size of 8mm, and 50g of anode fine powder with a particle size of -200 mesh, and mix them evenly to form the aggregate;
[0079] S2: Kneading: Add 20g of additive formula 4 to the aggregate prepared in step S1, and dry-mix in a kneader for 15min to obtain a uniformly mixed dry mixed material; then add 320g of coal tar pitch (softening point of 105°C, coking value of 58%) preheated to 180°C and wet-mix for 20min to obtain a uniformly kneaded paste;
[0080] S3: Molding: The anode paste obtained in step S2 is conveyed to a vibration molding machine for molding to form an anti-oxidation prebaked anode green body;
[0081] S4: calcination: the pre-baked anode green body obtained in step S3 is placed in a calcination furnace and calcined according to the set process heating curve: the heating rate in the low and high temperature stages is 8°C / h, the heating rate in the medium temperature stage is 10°C / h, the highest temperature of the calcination curve is 1190°C, the highest temperature of the sample is 1070°C, and the temperature is kept for 72h;
[0082] S5: Finished product: After roasting, the temperature is cooled to 150°C, and the metallurgical coke is cleaned out of the furnace to obtain an anti-oxidation pre-baked anode.
[0083] Example 5
[0084] An application of an additive in the preparation of a prebaked anode comprises the following steps:
[0085] S1: Batching: Accurately calculate the amount of each component of the anode paste, including 1680g of aggregate and 320g of binder; weigh 1546g of calcined petroleum coke (including 541g of 6# coke particles with a particle size of 5mm, 541g of 3# coke particles with a particle size of 2mm, and 464g of 1# coke particles with a particle size of 0.075mm), 84g of anode particles with a particle size of 8mm, and 50g of anode fine powder with a particle size of -200 mesh, and mix them evenly to form the aggregate;
[0086] S2: Kneading: Add 20g of additive formula 5 to the aggregate prepared in step S1, and dry mix in a kneader for 15min to obtain a uniformly mixed dry mixed material; then add 320g of coal tar pitch (softening point of 105°C, coking value of 58%) preheated to 180°C and wet mix for 20min to obtain a uniformly kneaded paste;
[0087] S3: Molding: The anode paste obtained in step S2 is conveyed to a vibration molding machine for molding to form an anti-oxidation prebaked anode green body;
[0088] S4: calcination: the pre-baked anode green body obtained in step S3 is placed in a calcination furnace and calcined according to the set process heating curve: the heating rate in the low and high temperature stages is 8°C / h, the heating rate in the medium temperature stage is 10°C / h, the highest temperature of the calcination curve is 1160°C, the highest temperature of the sample is 1050°C, and the temperature is kept for 72h;
[0089] S5: Finished product: After roasting, the temperature is cooled to below 180°C, and the metallurgical coke is removed from the furnace and cleaned to obtain an anti-oxidation pre-baked anode.
[0090] Example 6
[0091] An application of an additive in the preparation of a prebaked anode comprises the following steps:
[0092] S1: Batching: Accurately calculate the amount of each component of the anode paste, including 1680g of aggregate and 320g of binder; weigh 1546g of calcined petroleum coke (including 541g of 6# coke particles with a particle size of 5mm, 541g of 3# coke particles with a particle size of 2mm, and 464g of 1# coke particles with a particle size of 0.075mm), 84g of anode particles with a particle size of 8mm, and 50g of anode fine powder with a particle size of -200 mesh, and mix them evenly to form the aggregate;
[0093] S2: Kneading: Add 20g of additive formula 6 to the aggregate prepared in step S1, and dry-mix in a kneader for 15min to obtain a uniformly mixed dry mixed material; then add 320g of coal tar pitch (softening point of 105°C, coking value of 58%) preheated to 180°C and wet-mix for 20min to obtain a uniformly kneaded paste;
[0094] S3: Molding: The anode paste obtained in step S2 is conveyed to a vibration molding machine for molding to form an anti-oxidation prebaked anode green body;
[0095] S4: calcination: the pre-baked anode green body obtained in step S3 is placed in a calcination furnace and calcined according to the set process heating curve: the heating rate in the low and high temperature stages is 8°C / h, the heating rate in the medium temperature stage is 9°C / h, the highest temperature of the calcination curve is 1190°C, the highest temperature of the sample is 1050°C, and the temperature is kept for 70h;
[0096] S5: Finished product: After roasting, cool down to below 160°C, remove the metallurgical coke from the furnace and clean it to obtain an anti-oxidation prebaked anode.
[0097] Comparative Example
[0098] S1: Batching: Accurately calculate the amount of each component of the anode paste, including 1680g of aggregate and 320g of binder; weigh 1546g of calcined petroleum coke (including 541g of 6# coke particles with a particle size of 5mm, 541g of 3# coke particles with a particle size of 2mm, and 464g of 1# coke particles with a particle size of 0.075mm), 84g of anode particles with a particle size of 8mm, and 50g of anode fine powder with a particle size of -200 mesh, and mix them evenly to form the aggregate;
[0099] S2: Kneading: The aggregate prepared in step S1 is dry-mixed in a kneader for 15 minutes to obtain a uniformly mixed dry mixed material; then 320g of coal tar pitch (softening point of 105°C, coking value of 58%) preheated to 180°C is added and wet-mixed for 20 minutes to obtain a uniformly kneaded paste;
[0100] S3: Molding: The anode paste obtained in step S2 is conveyed to a vibration molding machine for molding to form a prebaked anode green body;
[0101] S4: calcination: the pre-baked anode green body obtained in step S3 is placed in a calcination furnace and calcined according to the set process heating curve: the heating rate in the low and high temperature stages is 8°C / h, the heating rate in the medium temperature stage is 10°C / h, the highest temperature of the calcination curve is 1160°C, the highest temperature of the sample is 1050°C, and the temperature is kept for 72h;
[0102] S5: Finished product: After roasting, the temperature is cooled to below 180°C, and the metallurgical coke is cleaned out of the furnace to obtain a pre-baked anode.
[0103] Test example
[0104] The performance parameters of the anti-oxidation prebaked anodes obtained in the above examples and comparative examples are compared, as shown in the following table:
[0105] Table 1: Comparison of performance indicators of prebaked anodes in embodiments and comparative examples:
[0106]
[0107]
[0108] The results show that the performance parameters of the antioxidant prebaked anode prepared using the 1-6 additive formula are significantly better than those of the comparative example, and can reach the first-class standard in the YS / T285-2022 "Prebaked Anode for Aluminum Electrolysis" standard, and focus on improving the CO2 reactivity and air reactivity of the anode. When using additive formula 5, namely: 11.75g boric acid, 1.50g carbon black, 4.42g aluminum silicate, 2.33g magnesium carbonate, the CO2 reaction residual rate and air reaction residual rate of the antioxidant prebaked anode are 98.50% and 96.14%, respectively, while the CO2 reaction residual rate and air reaction residual rate of the comparative example are 89.77% and 84.52%, respectively, which is significantly higher than the comparative example. The additive prepared by the present invention can effectively reduce the consumption of carbon anodes, reduce slag, and extend the service life of anodes, and has a wide range of applications and promotion value.
Claims
1. An additive for prebaked anodes, characterized in that: The components include the following by weight percentage: Boric acid: 30-60%; Carbon black: 1-11%; Stabilizer: 29-69%.
2. The additive according to claim 1, characterized in that: The stabilizer is one or more of aluminum silicate, aluminum fluoride, magnesium carbonate, magnesium oxide and mullite; and the particle size of the stabilizer is ≤2000 meshes.
3. The method for preparing the additive according to claim 1, characterized in that: The raw material components can be mixed and blended evenly to obtain the product.
4. Use of the additive according to claim 1 or 2 in the preparation of prebaked anodes.
5. The method for using the additive in the preparation of prebaked anode according to claim 1 or 2, characterized in that: The specific steps include: S1: Batching: Accurately calculate the amount of each component of the anode paste, of which the aggregate accounts for 80-90% by weight and the binder accounts for 10-20% by weight; weigh the calcined petroleum coke particles, anode particles, and anode fine powder respectively, and mix them evenly to form the aggregate; S2: Kneading: Add 0.1-2% additives to the aggregate prepared in step S1, dry-mix in a kneader to obtain a uniformly mixed dry mixed material; then add the preheated binder and wet-mix to obtain a uniformly kneaded anode paste; S3: Molding: The anode paste obtained in step S2 is transported to a vibration molding machine for molding to form an anti-oxidation prebaked anode green body; S4: calcining: placing the pre-baked anode green body obtained in step S3 in a calcining furnace and calcining it according to a set process heating curve; S5: Finished product: After roasting, the temperature is cooled to below 200°C, and the metallurgical coke is cleaned out of the furnace to obtain an antioxidant prebaked anode.
6. The method for using the additive in the preparation of prebaked anodes according to claim 5, characterized in that: The aggregate in step S1 comprises 86-94% calcined petroleum coke, 4-8% anode particles and 2-6% anode fine powder by weight.
7. The method for using the additive in the preparation of prebaked anodes according to claim 5, characterized in that the steps S1 The calcined petroleum coke is composed of a mixture of calcined coke particles of different particle sizes, wherein by weight percentage, 6# coke particles with a particle size of 6-3mm account for 30-40%, 3# coke particles with a particle size of 3-1mm account for 30-50%, and 1# coke particles with a particle size of 1-0.075mm account for 10-40%; the particle size of the anode particles is 7-9mm; and the particle size of the anode fine powder is 200-300 mesh.
8. The method for using the additive in the preparation of prebaked anodes according to claim 5, characterized in that: The binder in step S2 is coal tar, which has a softening point of 103-110° C. and a coking value of 56-59%.
9. The method for using the additive in the preparation of prebaked anodes according to claim 5, characterized in that: The dry mixing time in step S2 is 15-20 minutes; the preheating temperature is 178-186° C.; and the wet mixing time is 15-20 minutes.
10. The method for using the additive in the preparation of prebaked anodes according to claim 5, characterized in that: The process control parameters of the roasting step in step S4 are: the heating rate in the low-temperature and high-temperature stages is 7-10°C / h, the heating rate in the medium-temperature stage is 6-11°C / h, the highest temperature of the roasting curve is 1140-1200°C, the highest temperature of the sample is 1050-1080°C, and the insulation time is 48-84h.
Citation Information
Patent Citations
Preparation method of prebaked anode for rare earth additive modified aluminum
CN111041527A